Entwicklungen in slavischen Sprachen 1 - Lehmann, Volkmar (Specimina philologiae Slavicae, 1999)
This anthology is based on the work of the same-named Working Group "Developments in Slavic Languages" (E1SS). This working group, the "ElSS Salon", was founded in October 1995. Starting from the general basic assumptions that the structure of linguistic categories can be explained by the cognitive processing of reality, by the communicative function of utterances, and by their development, one sets oneself the joint occupation with the reconstruction of linguistic developments , with their description possibilities, regularities and explanations to the goal. Development means both diachrony and ontogenesis, as the basis of which the same principles can be assumed. In the context of this question, basic as well as individual questions, methodical and concrete application, both own research and the results of the relevant literature are discussed.